Stability of the Neuron Model Based on the Equation with Delay - Yu. V. Bogomolov (Моделирование и анализ информационных систем)
We analyze the periodical solution of a differential equation with delay describing the neuron-autogenerator dynamics. The stability of the periodical solution of the equation with certain param¬eters is investigated.